Beneficial effect of Re doping on the electrochemical HER activity of MoS2 fullerenes1. Issue 37 (7th October 2015) - Chhetri, Manjeet; Gupta, Uttam; Yadgarov, Lena; Rosentsveig, Rita; Tenne, Reshef; Rao, C. N. R.
<x xml:space="preserve">Abstract</x> The combined synergistic effect of Re doping and the IF structure on MoS2 for enhancing the electrochemical hydrogen evolution reaction.